Drying kinetics, colour change and menthol content in American peppermint dried by microwave vacuum dryer - P. Khamkon (2018)
American peppermint (Mentha piperita) is a source of essential oil, especially menthol. Dried American peppermint leaves can be used potentially to formulate mixed herbal tea. This study was conducted to investigate the quality and drying kinetics of American peppermint dried by microwave vacuum dryer. American peppermint leaves were dried at microwave power of 800, 1600 and 2400 W. Moisture content, colour (L, a, b) and menthol content in the samples were measured to optimize the drying parameter. It was found that drying time decreased with increased microwave power and the values of L, aand b in dried samples were lower than those of fresh samples. Moreover, those values increased with a decrease in microwave power. However, there was no significant difference between samples dried at 800-1.600 W. Menthol content in microwave dried samples decreased with an increase in microwave power. Regression analysis on drying kinetics showed that Page model gave the best result to represent satisfactorily microwave vacuum drying of American peppermint. © ISHS.